Generation of induced pluripotent stem cells from Bornean orangutans - Li, Chia-Jung; Chang, Chia-Chun; Tsai, Li-Kuang; Peng, Min; Lyu, Wei-Ni; Yu, Jane-Fang; Tsai, Mong-Hsun; Sung, Li-Ying (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Orangutans, classified under the Pongo genus, are an endangered non-human primate (NHP) species. Derivation of induced pluripotent stem cells (iPSCs) represents a promising avenue for conserving the genetic resources of these animals. Earlier studies focused on deriving orangutan iPSCs (o-iPSCs) from Sumatran orangutans (Pongo abelii). To date, no reports specifically target the other Critically Endangered species in the Pongo genus, the Bornean orangutans (Pongo pygmaeus). Methods: Using Sendai virus-mediated Yamanaka factor-based reprogramming of peripheral blood mononuclear cells to generate iPSCs (bo-iPSCs) from a female captive Bornean orangutan. In this study, we evaluate the colony morphology, pluripotent markers, X chromosome activation status, and transcriptomic profile of the bo-iPSCs to demonstrate the pluripotency of iPSCs from Bornean orangutans. Results: The bo-iPSCs were successfully derived from Bornean orangutans, using Sendai virus-mediated Yamanaka factor-based reprogramming of peripheral blood mononuclear cells. When a modified 4i/L/A (m4i/L/A) culture system was applied to activate the WNT signaling pathway in these bo-iPSCs, the derived cells (m-bo-iPSCs) manifested characteristics akin to human naive pluripotent stem cells, including high expression levels of KLF17, DNMT3L, and DPPA3/5, as well as the X chromosome reactivation. Comparative RNA-seq analysis positioned the m-bo-iPSCs between human naive and formative pluripotent states. Furthermore, the m-bo-iPSCs express differentiation capacity into all three germlines, evidenced by controlled in vitro embryoid body formation assay. Discussion: Our work establishes a novel approach to preserve the genetic diversity of endangered Bornean orangutans while offering insights into primate stem cell pluripotency. In the future, derivation of the primordial germ cell-like cells (PGCLCs) from m-bo-iPSCs is needed to demonstrate the further specific application in species preservation and broaden the knowledge of primordial germ cell specification across species.